A Mobile Web Application Engine for Generating Destination-oriented LRT Route - Abdullah, Muhammad Haziq Lim; Saifudin, Wan Sazli Nasaruddin; Hussin, Burairah; Abdul-Aziz, Azlianor; Sulong, Muhammad Suhaizan; Kamalrudin, Massila (2009)
Integrated Light Rail Transit (LRT) System in the capital of Malaysia connects some key districts to historical places, interesting places, business areas and shopping malls are concentrated. The train services are running independently but have interchanges to integrate from one different LRT lines. This may leads the traveler facing difficulty when they are choosing incorrect destination station especially on different LRT lines which contribute to time consuming and high costing. In previous research we already implement the mobile web application architecture where the destination-oriented routes need to be dynamically generated by determining the nearest station according to the specific places. In this paper, we proposed the used of Dijkstra’s Algorithms to provide more effective and intelligent shortest path system to provide the solution for traveler to reach the desired destination.